Student's awareness on gender issues through chick flicks : a case study in Kelantan, Malaysia - Iwan Zahar; Nur Hafezah Hussein (2013)
This article discusses issues involved in teaching gender issues through chick flicks among multimedia students at Faculty of Creative Technology and Heritage, Universiti Malaysia Kelantan. Nine multimedia students in their fourth year at the university, age 24 years old, in which 7 Malay students (five females) and 2 Malaysian Chinese students (1 female) were examined in their movies appreciation with relation to gender issues. The findings underlined three major problems; first, they seldom learn art criticism or movie critics and it was their first time to appreciate movies; second, 30% of the students were not proficient in English and have difficulties in reading the materials. Third, they have never been explained on gender issues in their courses